Cyclic Meditation and Sleep Quality: A Review - Boopalan, Deenadayalan; Vijayakumar, Venugopal; Karuppasamy, Govindasamy; Dilpreet, Kaur; Ravi, Poornima; Ponnusamy, Yogalakshmi; Vanamoorthy, Mahesh kannan; Kuppusamy, Maheshkumar (Sleep Science, 2024)
Objectives Insufficient sleep leads to several short- and long-term physical and mental consequences. Yoga is a popularly known complementary health approach that maintains physical and mental health through asanas, meditation, and breathing techniques. Cyclic meditation (CM), derived from one of the Upanishads, is practiced by combining physical postures (asanas) with relaxation techniques. Recent findings emphasize the significance of CM as a means to enhance sleep quality. The current review aims to find the effects of CM on sleep quality through the available scientific data.Methods The current review includes research articles evaluating CM's effect on sleep quality from various databases such as PubMed, Cochrane, Embase, and Google Scholar up to January 22, 2023. We conducted a literature search using keywords related to CM and sleep quality, and search results were restricted to studies published in the English language.Results There were 5 articles with 277 participants meeting inclusion criteria, all conducted in India. Of those, 2 were randomized controlled trials and 3 were single-group or two-group pre-post and crossover studies. Participants ranged from healthy volunteers, type-2 diabetic patients, alcohol dependents, and caregivers for special needs children. Based on the available scientific evidence, CM has been found to be effective (d = 0.56–4.90) in enhancing the quality of sleep.Conclusion The CM technique could be tentatively considered as a beneficial practice to improve sleep. However, further, adequately powered, and randomized controlled studies with various other parameters of sleep are required to strongly recommend CM as a stand-alone yogic intervention for sleep disturbance.
Keywords: cyclic meditation; mind-body practice; review; sleep quality; yoga